Inculcating the Entrepreneurial Skills Sets among the Students of Management Education in Chennai - Rengamani, .J.; Shameem, A. (International Journal of Psychosocial Rehabilitation, 2020)
The Entrepreneurial ability of an individual is considered to be the most vital thing for initiating a business venture or nurturing a new business idea. The entrepreneurial ability will make the individuals to have new startups so as to bring new products or services to the society. This will enable more business ventures to be initiated in a region and thereby the need for searching of jobs will drastically get reduced. It is always better to be a job giver than a job seeker. The entrepreneurial ability will pave way for giving jobs to many people. The entrepreneurial skills must be imbibed into the minds of the young engineering graduates. The entrepreneurial skill sets of the students must be identified and developed by the engineering institutions through modern educational technology. The students who are pursuing the engineering courses would find it easier to bring out the new products to the market since they know the nuances of production technology. In order to create interest among the students of engineering institutions, the training must be given in an efficient manner. The study aims to uncover the factors that are responsible for the entrepreneurial skill development among the students who are pursuing the engineering courses in various institutions located in Chennai.